Phylogenetic and Phylogenomic Definition of Rhizopus Species. Issue 6 (1st June 2018) - Gryganskyi, Andrii P; Golan, Jacob; Dolatabadi, Somayeh; Mondo, Stephen; Robb, Sofia; Idnurm, Alexander; Muszewska, Anna; Steczkiewicz, Kamil; Masonjones, Sawyer; Liao, Hui-Ling; Gajdeczka, Michael T; Anike, Felicia; et al.
Abstract: Phylogenomic approaches have the potential to improve confidence about the inter-relationships of species in the order Mucorales within the fungal tree of life. Rhizopus species are especially important as plant and animal pathogens and bioindustrial fermenters for food and metabolite production. A dataset of 192 orthologous genes was used to construct a phylogenetic tree of 21 Rhizopus strains, classified into four species isolated from habitats of industrial, medical and environmental importance. The phylogeny indicates that the genus Rhizopus consists of three major clades, with R. microsporus as the basal species and the sister lineage to R. stolonifer and two closely related species R. arrhizus and R. delemar . A comparative analysis of the mating type locus across Rhizopus reveals that its structure is flexible even between different species in the same genus, but shows similarities between Rhizopus and other mucoralean fungi. The topology of single-gene phylogenies built for two genes involved in mating is similar to the phylogenomic tree. Comparison of the total length of the genome assemblies showed that genome size varies by as much as threefold within a species and is driven by changes in transposable element copy numbers and genome duplications.